PENGARUH LAMA PENYINARAN MENGGUNAKAN LAMPU LED TERHADAP PRODUKTIVITAS FODDER HANJELI (Coix lacryma-jobi L.) HIDROPONIK - Gina Salma Alghaniya; Lizah Khairani; Iin Susilawati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
A hydroponic indoor planting systems needs manipulation of artificial lighting so that plants can produce optimal growth and production, one of it is by manipulating the length of irradiation using Light Emitting Diode (LED) lamps. This study aims to know the effect of irradiation length using LED lights on the productivity of Job’s Tears fodder in hydroponic planting system. The research was conducted on January - February 2020 at Laboratory of Forage Crops, Faculty of Animal Husbandry, Padjadjaran University. Completely Randomized Design (CRD) was used in this experiment with three irradiation length treatments (P1 = 12 hours of irradiation; P2 = 16 hours of irradiation; and P3 = 20 hours of irradiation) with 6 replications. The data was analyzed by analysis of variance (ANOVA) and Duncan analysis. The results of statistical analysis showed that the length of irradiation using LED lights did not affect to Job’s Tears fodder productivity of plant length, plant height, and dry matter production.